Anthropogenic Influence on the Antarctic Mesospheric Cooling Observed during the Southern Hemisphere Minor Sudden Stratospheric Warming - Sunkara Eswaraiah; Kyong-Hwan Seo; Kondapalli Niranjan Kumar; Madineni Venkat Ratnam; Andrey V. Koval; Jin-Yun Jeong; Chalachew Kindie Mengist; Young-Sook Lee; Katelynn Greer; Jun-Young Hwang; Wonseok Lee; Maniyattu Pramitha; et al. (Atmosphere, 2022)
Processes behind Sudden Stratospheric Warming (SSW), which occurs more frequently in the northern hemispheric polar latitudes and its influence from the stratosphere to the upper atmosphere are well documented. However, physical processes associated with SSW, although it ensues rarely in the southern hemisphere (SH), have a strong influence on the background atmosphere from the stratosphere to the mesosphere and are poorly understood. Using a ground-based meteor radar, satellite-borne Microwave-Limb sounder, and Modern-Era Retrospective Analysis for Research and Applications observations, we identified cooling of Antarctic mesopause by 26 K in response to a 66 K warming in the polar stratosphere during the 2019 minor SSW in the SH. The observed cooling is attributed to the interplay between planetary waves, CO2 infrared cooling, and O3 depletion, rather than adiabatic cooling due to gravity waves alone during SSW. It is proposed that anthropogenic and other sources generating chemical tracers in the lower atmosphere have caused mesospheric cooling and could be transported from the lower atmosphere both vertically and meridionally through residual mean meridional circulation from the tropics. Therefore, our study for the first time demonstrates the effect of lower atmosphere chemistry on the polar mesosphere thermal structure during the 2019 SSW.